Political Science and the Marcos Dictatorship - Abinales, Patricio N. (Archīum Ateneo, 2017)
This essay examines the position of political science as a discipline during the Marcos dictatorship. It explores the variations in political scientists’ approach to Marcos. Some approved and justified authoritarian rule, while others tried to elevate the political events to the level of “theory.” There was hardly any critique of the dictatorship in part because political scientists’ interpretation of the world did not dovetail with realities on the ground. Studies critical of martial law came from somewhere else, spearheaded by former political detainees who dabbled in dependency theory and did field research, leaving the discipline catching up with these non-political scientists until the end of martial law.